Analysis of Bilibili Company’s Business Strategy - Ji, Zefang (Transactions on Social Science, Education and Humanities Research, 2024)
This paper presents a detailed examination of Bilibili Inc.’s strategic framework, positioning the company as a formidable player in China’s digital entertainment sector. Bilibili has carved out a niche in the competitive landscape through its innovative approaches to community engagement, content diversification, strategic alliances, monetization strategies, and technological investments. The core of Bilibili’s success lies in its community-centric model, which prioritizes user-generated content (UGC) and interactive features, creating a highly engaged user base. This is complemented by the platform’s diverse content ecosystem across various genres, catering to a broad audience spectrum and fostering a rich content creation environment. Strategic partnerships with content creators, media firms, and technological entities have further augmented Bilibili’s content offerings and expanded its reach into new markets. Moreover, the company’s adaptive monetization models, including premium memberships and e-commerce, illustrate its innovative approach to generating revenue while enhancing user experience. Investment in cutting-edge technology underpins these strategic pillars, facilitating personalized content delivery and seamless user interactions. This paper synthesizes these dimensions to understand their collective impact on Bilibili’s growth trajectory and market dominance. Through this analysis, we aim to provide insights into the strategies digital entertainment platforms can employ to thrive in a rapidly evolving industry, highlighting the significance of community engagement, content versatility, and technological agility. Bilibili’s journey offers a compelling case study on sustaining competitive advantage and fostering long-term growth in the digital age.